Analytical Investigation of the Possible Chemical Interaction of Methyldopa with Some Reducing Carbohydrates Used as Pharmaceutical Excipients - Mohammad Reaz Siahi; Soma Rahimi; Farnaz Monajjemzadeh (Tabriz University of Medical Sciences, 2018)
Purpose: Assessment of drug substance and excipients compatibility is an important issue during pre-formulation studies as well as the quality control of pharmaceutical dosage forms. In this study, potential incompatibility between methyldopa and reducing excipients was evaluated using physicochemical methods. Methods: Dextrose and lactose (anhydrous & monohydrate) were selected as reducing carbohydrates. The initial incompatibility was studied with DSC and FTIR on binary mixtures with 1:1 mass ratio. Results were confirmed using HPLC studies coupled with mass spectrometry. Results: The DSC curves indicated the elimination of the melting endotherm of methyldopa in the binary mixtures. A new peak at 1719 cm-1 was observed in the FTIR spectra that can be attributed to the loss of type one amine functionality. The m/z of the proposed compound was observed in the mass spectra. Conclusion: The potential incompatibility of Methyldopa with reducing carbohydrates was established using physicochemical methods.